Alexandre Flückiger, Tracing the Evolutionary Path of Experimental Law: from Comparative Law to Regulatory Sandboxes „Acta Universitatis Carolinae – Iuridica” 2024, vol. 70, no. 2 - Dąbrowski, Karol (Studia Prawa Publicznego, 2024)
Alexandre Flückiger, Tracing the Evolutionary Path of Experimental Law: from Comparative Law to Regulatory Sandboxes (Śledzenie ewolucyjnej ścieżki eksperymentalnego prawa: od prawa porównawczego do regulacyjnych piaskownic), „Acta Universitatis Carolinae – Iuridica” 2024, vol. 70, no. 2, s. 13–22, https://doi.org/10.14712/23366478.2024.19 (opr. Karol Dąbrowski).